Ultra structural Description of Young Corn (Zea mays L) Ear - Nik Fakurudin, N. A.; Solihah, M.A.; Wan Rosli, W. I. (Microscopy Society of Singapore, 2013)
Young corn (Zea mays L) ears are small, immature indehiscent fruits that do not open spontaneously at maturity to release seeds. The present ultra structural study was conducted to examine detailed surface structure topography of the young corn ear. Macroscopic observation was done on fresh young corn ears prior to dry-gross sectioning. They were viewed using variable pressure scanning electron microscope (VPSEM). Observation of the longitudinal and horizontal section shows manifestation of anomalous appearances of the pedicel of the cotyledon. The actual area of growth of the corn silk base mimics the structured formation of matured corn fruit were seen in all micrographs. The ultra structures of the young corn ears consist of the pith cell, pedicel, corn silk roots and pericarp of the cotyledon. Corn silks also present as a single hollow tubular strand with longitudinally-oriented array tubes at every pedicel. The size of these corn silks strands vary between 6-8 μm in diameter. These findings are the first recording describing the VPSEM analysis of the surface ultra structure topography of young corn ears.